Model of nursing care for patients with Brugada syndrome according to the international ICNP® - Stosiek, Aleksandra; Pryszcz, Jowita; Budzyna-Dawidowski, Dominik; Jankowska-Polańska, Beata (Journal of Education, Health and Sport, 2019)
IntroductionBrugada syndrome is a rare disease involving genetic disorders of heart rhythm. The disease was discovered in 1992 by the Brugada brothers, Spanish cardiologists. This syndrome occurs with sporadic frequency in families with 5-66/10,000 affected worldwide, and 12/10,000 affected in Asia. Usually, the disease affects people between the age of 30 and 50 years of age. Brugada syndrome is responsible for 4-12% of all sudden cardiac arrests, and 20% of sudden cardiac arrest patients who have never had organic cardiovascular disease. The pathomechanism of this syndrome is not fully understood, but three types of factors can be distinguished: genetic, hormonal and environmental. The most common mutation causing Brugada Syndrome is the mutation of SCN5A gene. Brugada syndrome is characterized by the occurrence of syncope episodes and pre-osmotic states along with sudden cardiac arrest, which is a result of ventricular arrhythmias. The basis for the diagnosis of Brugada syndrome is the use of a 12-lead ECG and in some cases, pharmacological diagnosis, consisting of simultaneous monitoring of ECG and administration of a class I antiarrhythmic drug according to Vaughan-Williams classification. Treatment of Brugada syndrome consists of implantation of a cardioverted-defibrillator (ICD) in accordance with criteria (I, IIa and IIb), based, inter alia, on the patient’s state of health and course of cardiovascular arrest. Prognosis in asymptomatic patients is largely positive. AimThe aim of the study was to use the international ICNP® classification when presenting the problems in nursing care in patients with Brugada syndrome. Materials and MethodsThe nursing care model based on the international ICNP® classification was used. The diagnoses were based on symptoms and problems of patients with Brugada syndrome.Summary Although the Brugada syndrome is a rare disease entity, it should be taken into account when differentiating other factors which may lead to sudden cardiac arrest. Due to prodromal nonspecific symptoms, care should be taken into accurately diagnosing with 12-lead ECGs. The most common problems in patients with Brugada syndrome are palpitations (frequently occurring at night), fainting, and at the same time risk of falling and chest pain. Healthcare professionals caring for patients with Brugada syndrome should observe the patient for the first signs of fainting, prioritizing safety. ConclusionsBrugada syndrome is a rare disease with nonspecific symptoms, which is why accurate diagnostic methods, including primarily tech 12-lead ECG are of great importance. Diagnostics, along with appropriate education of the patient and their families, allow effective care and prevention against the occurrence of negative effects of this disease.